Unexpected Simple and Catalyst‐Free Condensation Reaction of Spiro Dihydrofurans with 2, 4‐Dinitrophenylhydrazine, Thiosemicarbazide, and Hydroxylamine for the Synthesis of Novel Corresponding 4, 4, 6′, 6′‐Tetramethyl‐3′‐aryl‐3′, 5′, 6′, 7′‐tetrahydrospiro[cyclohexane‐1, 2′‐indole]‐4′, 6(1′H)‐diones: Crystal Structure. (11th September 2018) - Zhian, Hassan; Noroozi Pesyan, Nader; Aalinejad, Michael; Rashidnejad, Hamid; Notash, Behrouz
Abstract : The reaction of 4′, 4′, 6, 6‐tetramethyl‐3‐aryl‐3, 5, 6, 7‐tetrahydro‐4 H ‐spiro[benzofuran‐2, 1′‐cyclohexane]‐2′, 4, 6′‐trione with 2, 4‐dinitrophenylhydrazine, thiosemicarbazone, and hydroxylamine afforded unexpectedly novel corresponding 4, 4, 6′, 6′‐tetramethyl‐3′‐aryl‐3′, 5′, 6′, 7′‐tetrahydrospiro[cyclohexane‐1, 2′‐indole]‐4′, 6(1′ H )‐diones in ethylene glycol in reflux and catalyst‐free condition. The structure is characterized using FT‐IR, 1 H, 13 C NMR, elemental analysis, mass spectrometer, and X‐ray crystallography techniques. Abstract :